2018
DOI: 10.7567/jjap.57.106601
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phonon deformation potentials and strain-shift coefficients in Ge-rich Si1− x Ge x using bulk Ge-rich Si1− x Ge x crystals and oil-immersion Raman spectroscopy

Abstract: The strain-free Raman shift of the Ge–Ge mode, , of Ge-rich Si1−xGex (x: Ge fraction) was determined accurately from the bulk Ge-rich Si1−xGex samples fabricated by the Czochralski (Cz) method. Using the obtained , the phonon deformation potentials (PDPs), p and q, and the strain-shift coefficient bLO of isotropic biaxial strained Ge-rich Si1−xGex thin films were extracted by oil-immersion Raman spectroscopy using Raman peak shifts of longitudinal and transverse optical (LO and TO) phonon modes. As a result, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
(106 reference statements)
2
11
0
Order By: Relevance
“…On the other hand, we have already shown that the Ge-Ge mode for the Ge-rich SiGe thin film and confirmed no LVMs around the lower wavenumber side (260 ⩽ ω ⩽ 310) by oil-immersion Raman spectroscopy to determine the strain-shift coefficient and phonon deformation potentials in our previous study. 28) These results are in good agreement in ab initio calculations reported by Pagès and coworkers. 29) Pagès and coworkers have also reported the change in frequency or intensity of main (Si-Si, Si-Ge, and Ge-Ge) and minor (LVMs) Raman features by percolation/onedimensional-cluster scheme and ab initio calculations.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, we have already shown that the Ge-Ge mode for the Ge-rich SiGe thin film and confirmed no LVMs around the lower wavenumber side (260 ⩽ ω ⩽ 310) by oil-immersion Raman spectroscopy to determine the strain-shift coefficient and phonon deformation potentials in our previous study. 28) These results are in good agreement in ab initio calculations reported by Pagès and coworkers. 29) Pagès and coworkers have also reported the change in frequency or intensity of main (Si-Si, Si-Ge, and Ge-Ge) and minor (LVMs) Raman features by percolation/onedimensional-cluster scheme and ab initio calculations.…”
Section: Resultssupporting
confidence: 90%
“…In this study, we only investigated Raman spectra for Ge-Ge vibration modes since the Raman spectral intensities of Si-Si and Si-Ge vibration modes were lower than that of Ge-Ge vibration modes as the SiGe NW is rich in Ge. In general, the Raman peak of the Ge-Ge vibration mode in the SiGe alloy is observed 31,36) at around the lower wavenumber side than 301 cm −1 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum consisted of three components. Considering the Raman spectra of pure Si, SiGe and Ge, 24,25) the peaks around 295, 405, and 460 cm −1 were assigned to the Ge-Ge, Si-Ge, and Si-Si modes, respectively. Each excitation peak intensity reflected the fraction of Si and Ge atoms.…”
Section: Raman Spectrummentioning
confidence: 99%